Nest site selection of the White-backed Woodpecker Dendrocopos leucotos in the eastern part of Latvia - Krams, Indrikis (Ornis Svecica, 1998)
The White-backed Woodpecker Dendrocopos leucotos shows decreasing population trends in most areas in Europe. The main reason for this is increasing activity of man in changing the species' habitat. My study on the distribution and breeding biology of the White-backed Woodpecker in the eastern part of Latvia provides some evidence that these local woodpeckers live in stable populations. In view of this, it is important to begin more serious studies on the Latvian White-backed Woodpeckers to develop successful protection programmes which could be useful also for the whole of northern Europe.